The Influence of Drill Method and Audio Visual Media on Badminton Short Service Strokes at SMPN 1 Tembelang Jombang - Zoki, Achmed; Ahmad, Nurdian (MAN Insan Cendekia Jambi, 2025)
The ability to perform short badminton service skills well is very necessary in badminton games, so an approach is needed, namely the drill method and audio-visual media which aims for students to master the service technique. The purpose of this study was to determine the effect of the drill method and audio-visual media on the short badminton service skills of class VIII-E students of SMPN 1 Tembelang Jombang. This type of research with Pre-experiment design through a quantitative approach using one group pretest-posttest design. The sample of this study was class VIII-E students of SMPN 1 Tembelang Jombang with 32 students. Based on the results of the study conducted by the researcher, the average pretest value was 24.81 which was categorized as sufficient and the average posttest result was 31.41 which was categorized as good. And from the calculation of SPSS version 25 with the paired sample t-test, the sig value (2-tailed) = 0.000 and <0.05 was found, so there was a significant difference before and after the treatment was given. So it can be concluded that there is a positive influence of the drill method and audio-visual media on the short service skills of badminton class VIII-E SMPN 1 Tembelang Jombang.